Beneficial Microorganisms for Corals (BMC): Proposed Mechanisms for Coral Health and Resilience - Peixoto, Raquel S.; Rosado, Phillipe M.; Leite, Deborah Catharine de Assis; Rosado, Alexandre S.; Bourne, David G. (Frontiers in Microbiology, 2017)
The symbiotic association between the coral animal and its endosymbiotic dinoflagellate partner Symbiodinium is central to the success of corals. However, an array of other microorganisms associated with coral (i.e., Bacteria, Archaea, Fungi and viruses) have a complex and intricate role in maintaining homeostasis between corals and Symbiodinium. Corals are sensitive to shifts in the surrounding environmental conditions. One of the most widely reported responses of coral to stressful environmental conditions is bleaching. During this event, corals expel Symbiodinium cells from their gastrodermal tissues upon experiencing extended seawater temperatures above their thermal threshold. An array of other environmental stressors can also destabilize the coral microbiome, resulting in compromised health of the host, which may include disease and mortality in the worst scenario. However, the exact mechanisms by which the coral microbiome supports coral health and increases resilience are poorly understood. Earlier studies of coral microbiology proposed a coral probiotic hypothesis, wherein a dynamic relationship exists between corals and their symbiotic microorganisms, selecting for the coral holobiont that is best suited for the prevailing environmental conditions. Here, we discuss the microbial-host relationships within the coral holobiont, along with their potential roles in maintaining coral health. We propose the term BMC (Beneficial Microorganisms for Corals) to define (specific) symbionts that promote coral health. This term and concept are analogous to the term Plant Growth Promoting Rhizosphere (PGPR), which has been widely explored and manipulated in the agricultural industry for microorganisms that inhabit the rhizosphere and directly or indirectly promote plant growth and development through the production of regulatory signals, antibiotics and nutrients. Additionally, we propose and discuss the potential mechanisms of the effects of BMC on corals, suggesting strategies for the use of this knowledge to manipulate the microbiome, reversing dysbiosis to restore and protect coral reefs. This may include developing and using BMC consortia as environmental “probiotics” to improve coral resistance after bleaching events and/or the use of BMC with other strategies such as human-assisted acclimation/adaption to shifting environmental conditions.